Meta-analysis of HLA-DRB1 polymorphism in Latin American patients with rheumatoid arthritis (2007)
Objectives: To estimate the common effect size of HLA-DRB1 alleles on rheumatoid arthritis (RA) susceptibility across Latin America populations through a meta-analysis combining the results of published data. Methods: Case-control studies on HLA-DRB1 association with RA in Latin America were searched up to October 2006. Genotype frequencies were extracted according to both shared epitope (SE) and HLA-DR4 positive or negative alleles. The effect summary odds ratio (OR) and 95% confidence intervals was obtained. Heterogeneity and publication bias were assessed. Results: Eight studies containing 684 cases and 1015 controls were included. Under the random effects model, the common OR was 3.28 (1.93, 5.60) (p and lt; 0.0001) and 3.54 (2.47, 5.05) (p = 4.22 × 10- 12) for HLA-DR4 and SE, respectively. There was no evidence of publication bias according to Funnel plot and Egger's regression test (p = 0,445 for DR4 and p = 0,464 for SE meta-analysis). Significant heterogeneity was observed for HLA-DR4 (I2 = 81.06%, Q = 36.96, p = 0.000005) but not for the SE meta-analysis. Conclusions: HLA-DR4 and SE positive HLA-DRB1 alleles (mainly HLA-DRB1*0404) are associated with RA in Latin Americans. Heterogeneity is expected owing to the diverse degree of admixture between the examined populations. Our findings support the HLA as a major susceptibility locus for RA and validate the SE hypothesis in Latin America. © 2007 Elsevier B.V. All rights reserved.